2021
DOI: 10.1177/15480518211036464
|View full text |Cite
|
Sign up to set email alerts
|

Does Leader Humor Influence Employee Voice? The Mediating Role of Psychological Safety and the Moderating Role of Team Humor

Abstract: Past research indicates that leader humor can bring many positive outcomes; however, its influence on employee voice has been largely neglected. We propose that leader humor can influence employee voice behaviors (i.e., promotive and prohibitive) via the mediating role of psychological safety. Drawing upon the substitutes for leadership theory, we further propose that team humor could moderate the influence of leader humor. Based on the latent moderated mediation structural equation modeling analysis, we found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“… 4 Previous empirical studies have shown that companies with a strong safety climate closely associate employees with an organization’s psychological contract 26 and that those with a positive organization climate improve employee psychological safety. 27 Therefore, we propose hypothesis H2.…”
Section: Theoretical Basis and Hypothesesmentioning
confidence: 99%
“… 4 Previous empirical studies have shown that companies with a strong safety climate closely associate employees with an organization’s psychological contract 26 and that those with a positive organization climate improve employee psychological safety. 27 Therefore, we propose hypothesis H2.…”
Section: Theoretical Basis and Hypothesesmentioning
confidence: 99%
“…According to Ziv (1983), frequent use of affiliative humor in a group might be seen as a cue that triggers nonconventional thinking. Moreover, affiliative humor might reduce social distance as well as enhance psychological safety and team cohesion which translate into creativity and innovation in a team (Eliav et al, 2016;Hülsheger et al, 2009;Mesmer-Magnus et al, 2012;Potipiroon & Ford, 2021;Romero & Cruthirds, 2006). Overall, these studies offer evidence that affiliative team humor style, once it has emerged in a team, will result in team positive emotions, team cohesion, while providing a high level of psychological safety, which will then enhance the likelihood of team innovation.…”
Section: The Mediating Role Of Affiliative Team Humor Stylementioning
confidence: 99%
“…As a leader's behavior amuses subordinates by using humorous words and behaviors in interaction and communication with them (Yam et al, 2018), leader humor has received a wide range of attention in the field of management in recent years (Hughes and Avey, 2009;Neves and Karagonlar, 2020). A large and increasing body of research has substantiated the impact of leader humor on subordinates, including task performance (Neves and Karagonlar, 2020;Tan et al, 2021), job satisfaction (Robert et al, 2016), organizational citizenship behavior (Cooper et al, 2018;Tremblay and Gibson, 2016), voice behavior (Potipiroon and Ford, 2021;Tan et al, 2020), creativity (Peng et al, 2020;Yang et al, 2021), leader-member exchange (Pundt and Venz, 2017;Yam et al, 2018), relational identification and trust in leaders (Gkorezis and Bellou, 2016;Neves and Karagonlar, 2020). Notwithstanding such findings, with regard to the topic of newcomer adjustment, the question of whether and how leader humor may exert an influence on newcomers' adjustment has received little attention.…”
Section: Leader Humor and Newcomer Adjustment 1201mentioning
confidence: 99%
“…, 2016), organizational citizenship behavior (Cooper et al. , 2018; Tremblay and Gibson, 2016), voice behavior (Potipiroon and Ford, 2021; Tan et al. , 2020), creativity (Peng et al.…”
Section: Introductionmentioning
confidence: 99%